2011
DOI: 10.1007/s11258-011-9989-9
|View full text |Cite
|
Sign up to set email alerts
|

Variation of growth and functional traits of invasive knotweeds (Fallopia spp.) in Belgium

Abstract: Three invasive Fallopia taxa are present in Belgium: F. japonica (FJ), F. sachalinensis (FS) and their hybrid F. 9 bohemica (FB). FS is the least invasive of the three taxa. In this study, we compared the taxa, in sites where they co-occur, for differences in functional traits that might influence their competitive ability and invasiveness-shoot height and ramification, leaf size, specific leaf area (SLA) and foliar nitrogen (N) concentration. The three taxa exhibited similar growth kinetics and similar SLA. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 50 publications
(51 reference statements)
6
15
1
Order By: Relevance
“…In contradiction to other studies (e.g. [36,37]), where selected sites were more variable, the results revealed that sites located along the two rivers hardly differed in the studied soil parameters. Thus, it can be inferred that the sites did not affect the results, and permitted analyses across the two rivers.…”
Section: Environmental Requirements Of Fallopia Taxa and Accompanyingcontrasting
confidence: 99%
See 4 more Smart Citations
“…In contradiction to other studies (e.g. [36,37]), where selected sites were more variable, the results revealed that sites located along the two rivers hardly differed in the studied soil parameters. Thus, it can be inferred that the sites did not affect the results, and permitted analyses across the two rivers.…”
Section: Environmental Requirements Of Fallopia Taxa and Accompanyingcontrasting
confidence: 99%
“…With reference to the above, it can be stated that F. japonica is the most tolerant to high nitrogen variation in soil when compared to the remaining knotweed species. Concerning organic carbon, in our study soils were not very rich, as in the Belgium sites [36], but ours were more similar to the results obtained by Rahmonov et al [45] for F. japonica. Furthermore, the concentration of phosphorus in our soils was very variable as in sites in Belgium [36].…”
Section: Tabsupporting
confidence: 91%
See 3 more Smart Citations